Ideology in a Desert Landscape*. (11th October 2017) - Torza, Alessandro
Abstract: On one influential view, metaphysical fundamentality can be understood in terms of joint‐carving. Ted Sider has recently argued that (i) some first order quantifier is joint‐carving, and (ii) modal notions are not joint‐carving. After vindicating the theoretical indispensability of quantification against recent criticism, I will defend a logical result due to Arnold Koslow which implies that (i) and (ii) are incompatible. I will therefore consider an alternative understanding of Sider's metaphysics to the effect that (i) some first order quantifier is joint‐carving, and (iii) intensional notions are not joint‐carving. Another result due to Koslow entails that (i) and (iii) are also incompatible. I will argue that this second result is inconclusive. Nevertheless, (iii) is incompatible with another tenet of Sider's metaphysics, namely that (iv) 'being joint‐carving' is itself joint‐carving. In order to resolve the inconsistency, I will tentatively argue that condition (iv) should be renounced.